Undergraduate rural medical training experiences and uptake of rural practice: a retrospective cohort study in South Australia - Susan Williams; David Gonzalez-Chica; Katrina Morgan; Bronwyn Herde; Lawrie McArthur; Lucie Walters (BMC Medical Education, 2023)
Abstract Background Rural medical training experiences provided by Rural Clinical Schools (RCS) can encourage future practice in rural locations. However, the factors influencing students’ career choices are not well understood. This study explores the influence of undergraduate rural training experiences on graduates’ subsequent practice location. Methods This retrospective cohort study included all medical students who completed a full academic year at the University of Adelaide RCS training program between 2013–2018. Details of student characteristics, experiences, and preferences were extracted from the Federation of Rural Australian Medical Educators (FRAME, 2013–2018) survey and linked to graduates’ recorded practice location obtained from the Australian Health Practitioner Regulation Agency (AHPRA, January 2021). The rurality of the practice location was defined based on the Modified Monash Model (MMM 3–7) or Australian Statistical Geography Standard (ASGS 2–5). Logistic regression was used to examine associations between student rural training experiences and rural practice location. Results A total of 241 medical students (60.1% females; mean age 23.2 ± 1.8 years) completed the FRAME survey (response rate 93.2%). Of these, 91.7% felt well supported, 76.3% had a rural-based clinician mentor, 90.4% reported increased interest in a rural career, and 43.6% preferred a rural practice location after graduation. Practice locations were identified for 234 alumni, and 11.5% were working rurally in 2020 (MMM 3–7; 16.7% according to ASGS 2–5). In adjusted analysis, the odds of working rurally were 3–4 times more likely among those with a rural background or lived the longest in a rural location, 4–12 times more likely among those preferring a rural practice location after graduation, and increased with the student’s rural practice self-efficacy score (p-value < 0.05 in all cases). Neither the perceived support, having a rural-based mentor, or the increased interest in a rural career were associated with the practice location. Conclusions These RCS students consistently reported positive experiences and increased interest in rural practice after their rural training. Student reported preference for a rural career and rural practice self-efficacy score were significant predictors of subsequent rural medical practice. Other RCS could use these variables as indirect indicators of the impact of RCS training on the rural health workforce.